Factors Influencing the Nutritional Status of Pregnant Women Employed in Government Education and Health Institutions in Timor-Leste - Camões Pereira, Sofia; Umbu Roga, Anderias; Ratu, Jacob M. (Journal of Neonatal Surgery, 2025)
Poor nutritional status among pregnant women can increase the risk of low birth weight (LBW), growth delays, birth defects, and even death for both the mother and child. In 2020, approximately 287,000 women died during or after pregnancy and childbirth (WHO), with nearly 95% of all maternal deaths occurring in low- and lower-middle-income countries. Timor-Leste has one of the highest maternal mortality rates in Southeast Asia, at 195 per 100,000 live births. The aim of this research is to analyze the factors influencing the nutritional status of pregnant women employed in health and educational institutions within the Timor Leste government. This study employs a quantitative design with a cross-sectional survey approach. The study population consists of pregnant women with a gestational age of over 20 weeks, and the sample size includes 55 women. Convenience sampling was used, with a questionnaire as the data collection tool. The results of the chi-square statistical test show no significant relationship between physical workload (p value = 0.485), work stress level (p value = 0.310), knowledge level (p value = 0.087), and food perceptions (p value = 0.153) with the nutritional status of pregnant women working in education and health institutions in Timor Leste. However, a relationship was found between work fatigue (p value = 0.044) and the nutritional status of pregnant female workers. Therefore, interventions are necessary to reduce workplace fatigue in order to improve the nutritional and health status of pregnant women workers. Strategies focused on managing fatigue and reducing occupational risks should be prioritized to enhance their well-being and promote better pregnancy outcomes.